Do pre-existing diabetes social support or depressive symptoms influence the effectiveness of a diabetes management intervention?. Issue 11 (November 2015) - Rosland, Ann-Marie; Kieffer, Edith; Spencer, Michael; Sinco, Brandy; Palmisano, Gloria; Valerio, Melissa; Nicklett, Emily; Heisler, Michele
Highlights We examined how diabetes social support and depressive symptoms affected change in glycemic control over 6 months. Participants were randomized to a diabetes self-management intervention or usual care. Higher social support at baseline predicted larger improvements in glycemic control. These improvements were independent of intervention improvements in glycemic control. Baseline social support and depression levels did not change how effective the intervention was.